Constraints on Variscan and Cimmerian magmatism and metamorphism in the Pontides (Yusufeli-Artvin area), NE Turkey from U-Pb dating and granite geochemistry - Ustaomer, Timur; Robertson, Alastair H. F.; Ustaomer, P. Ayda; Gerdes, Axel; Peytcheva, Irena (GEOLOGICAL SOC PUBLISHING HOUSE, 2013)
Metamorphic and igneous rocks exposed in NW-vergent thrust sheets and their auto-cthonous basement in the NE Pontides were dated by the U-Pb method using zircons, supported by geochemical data for granitic rocks. Two meta-sedimentary units (Narlik schist and Karadag. paragneiss) yielded detrital zircon populations of 0.50-0.65 and 0.9-1.1 Ga, suggesting an affinity with NE Africa (part of Gondwana). The youngest concordant zircon age is Ediacaran for the schist but Devonian for the paragneiss, bracketing the paragneiss depositional age as Mid-Devonian to Early Carboniferous. Metamorphic rims of zircon cores in the paragneiss gave Carboniferous ages (345-310 Ma). The zircon rim data indicate two Variscan metamorphic events (334 and 314 Ma) separated by a hiatus (320-325 Ma). Granite emplacement took place during early Carboniferous, Early Jurassic and Late Jurassic phases. The crystallization age of the early Carboniferous granites (c. 325 Ma) corresponds to a hiatus in the zircon age data that could reflect subduction slab break-off. The Variscan granitic rocks intruded a Gondwana-derived continental terrane that was loosely accreted to Eurasia during early-late Carboniferous time but remained isolated from Eurasian-derived terrigenous sediment. In contrast, the Jurassic granitic magmatism relates to later back-arc extension along the southern margin of Eurasia.
Keywords: PLATE TECTONIC MODEL; UNIT BOHEMIAN MASSIF; PRE-ALPINE BASEMENT; BACK-ARC FORMATION; DETRITAL ZIRCONS; EASTERN PONTIDES; TRACE-ELEMENT; PULUR COMPLEX; GONDWANAN TERRANES; NORTHWEST TURKEY; Geochemistry & Geophysics; Geology